Greek Teachers' Approaches to Social Justice Based on Fraser's Model - Σόρκος, Γεώργιος; Λαζαρίδου, Αγγελική; Πολυμεροπούλου, Βασιλική; Ξαφάκος, Ευστάθιος (Education Sciences, 2021)
The purpose of the present quantitative research is to determine teachers' perceptions of their transformational capacity to promote social justice in both their rhetoric and their teaching practice. The reason for doing so is the recorded bibliographic assumption that the improvement and effectiveness of the school unit, in the current hyper-differentiated circumstances, require new and more complex roles for the teaching staff, with the implementation of programs related to social justice. Two hundred and nineteen primary and secondary teachers were asked to use a questionnaire to reflect on social justice issues through short case-study scenarios. The results of the research highlight teachers' orientation towards social justice. With regard to the individual dimensions of social justice, according to Nancy Fraser's theoretical model (1995, 1996, 2005), teachers focus more on issues related to redistribution and representation and, secondly, on recognition.